1976
DOI: 10.1103/physrevb.13.4396
|View full text |Cite
|
Sign up to set email alerts
|

Surface and volume photoemission spectral yield from silver

Abstract: We defined surface and volume components of photoemission and an experimental process to separate them. The reflectance, transmittance, and photoelectric yield were measured from silver thin films for p and s polarizations, for front and back illumination through the silica substrate, for angles of incidence ranging from 0' to 75', and for photon energy ranging from 3.5 to 4.5 eV. We calculate values of the index of refraction, the escape depth of the photoelectrons, and the surface to volume photoyield ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Plummer [9], Vernier [10] and Chabrier et al [11] have also considered the role of surface states in photoelectric emission. However Draine [12] has concluded that the role of these surface states is inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Plummer [9], Vernier [10] and Chabrier et al [11] have also considered the role of surface states in photoelectric emission. However Draine [12] has concluded that the role of these surface states is inconclusive.…”
Section: Introductionmentioning
confidence: 99%